Kinase Control Prevents HIV-1 Reactivation in Spite of High Levels of Induced NF-κB Activity - Wolschendorf, Frank (American Society for Microbiology, 2012)
Despite its clinical importance, the molecular biology of HIV-1 latency control is at best partially understood, and the literature remains conflicting. The most recent description that latent HIV-1 is integrated into actively expressed host genes has further confounded the situation. This lack of molecular understanding complicates our efforts to identify therapeutic compounds or strategies that could reactivate latent HIV-1 infection in patients, a prerequisite for the eradication of HIV-1 infection. Currently, many therapeutic development efforts operate under the assumption that a restrictive histone code could govern latent infection and that either dissipation of the histone-based restrictions or NF-κB activation could be sufficient to trigger HIV-1 reactivation. We here present data that suggest an additional, higher level of molecular control. During a high-content drug screening effort, we identified AS601245 as a potent inhibitor of HIV-1 reactivation in latently infected primary T cells and T cell lines. In either system, AS601245 inhibited HIV-1 reactivation despite high levels of induced NF-κB activation. This finding suggests the presence of a gatekeeper kinase activity that controls latent HIV-1 infection even in the presence of high levels of NF-κB activity. Potential therapeutic stimuli that do not target this gatekeeper kinase will likely fail to trigger efficient system-wide HIV-1 reactivation.